2015
DOI: 10.3758/s13415-015-0341-z
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the relationships among filtering activity, unnecessary storage, and visual working memory capacity

Abstract: The amount of task-irrelevant information encoded in visual working memory (VWM), referred to as unnecessary storage, has been proposed as a potential mechanism underlying individual differences in VWM capacity. In addition, a number of studies have provided evidence for additional activity that initiates the filtering process originating in the frontal cortex and basal ganglia, and is therefore a crucial step in the link between unnecessary storage and VWM capacity. Here, we re-examine data from two prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(47 reference statements)
2
14
0
Order By: Relevance
“…It is unknown how flexible allocation would be reflected in this activity, but we suggest it is accomplished through those networks that mediate top-down attention and executive control. This proposal is consistent with the findings of Edin et al (2009) finding functional connectivity between frontal activity in the dorsolateral prefrontal cortex and the IPS, as well as the direct path found by Emrich and Busseri (2015) suggesting attention related activity plays a central role in VSTM performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is unknown how flexible allocation would be reflected in this activity, but we suggest it is accomplished through those networks that mediate top-down attention and executive control. This proposal is consistent with the findings of Edin et al (2009) finding functional connectivity between frontal activity in the dorsolateral prefrontal cortex and the IPS, as well as the direct path found by Emrich and Busseri (2015) suggesting attention related activity plays a central role in VSTM performance.…”
Section: Discussionsupporting
confidence: 92%
“…However looking at structures alone can only explains part of the mechanism. Emrich and Busseri (2015), tested the implied path from frontal regions controlling access (filtering) to storage activity in the parietal cortex that would predict working memory capacity using the data from McNab & Klingberg (2008). When they tested a path model, the direct path of from filtering activity to working memory capacity was a stronger predictor than the indirect path of frontal activity controlling access to memory storage (unnecessary storage) predicting VSTM performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Emrich and Busseri (2015) reanalyzed outcomes from McNab and Klingberg (2008) and Liesefeld et al (2014) , and found that individual differences in working memory capacity were predicted by filtering-related activity, rather than unnecessary storage of distractor items. Emrich and Busseri (2015) suggested that this filtering activity might reflect general top-down attentional control, and would be critical for the selection and processing of target items, even when to-be-ignored distractors are absent. Taking a slightly different approach, Shipstead et al (2014) distinguished between memory for visual arrays with and without additional distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent engagement of attentional control mechanisms is required in tasks of visual WM to prevent errors from complete attentional lapses and more subtle causes such as insufficient individuation of items or swapping item positions (Adam, Mance, Fukuda, & Vogel, 2015). Moreover, neural measures of attentional control also predict WMC directly (Emrich & Busseri, 2015). Both sleep deprivation and sleep restriction are known to result in deficits to sustained attention and executive control of attention (Durmer & Dinges, 2005), and such deficits may account for impaired WM under conditions of sleep loss (Frenda & Fenn, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they found in distractor-present conditions a negative-going peak about 245ms post-stimulus, and (although not analyzed in their report), a pattern of more positive amplitude on average over the second half of the delay period. Importantly, the activity associated with filtering processes has been shown to predict WMC independent of the presence of distractors, and it has been proposed that such activity may index the efficient processing of target information (Emrich & Busseri, 2015).…”
Section: Discussionmentioning
confidence: 99%